Reabilitação estético-funcional multidisciplinar: relato de caso clínico - PANCIERI, Kézia Rafaely Bravos (2019)
A harmonious smile is a fundamental requirement in modern social life, in such a way, that changing the normal pattern of dental structure directly implies the need for correc-tion. Obtaining a good diagnosis, treatment planning and therapeutic procedures, fa-vours a multidisciplinary rehabilitation, being able to have a complete overview of the treatment to be performed, as well as a coordination of several specialties to solve dif-ferent problems found within. Patient JRLR, 62 years old, male, brown, diabetic type II and controlled hypertension, sought the Faculty of Dentistry of the Federal University of Para (FO-UFPA) complaining mainly about the size and color of the teeth. The dam-ages in the color and / or shape of the teeth may be treated with the use of different methods, and the approach should always be as conservative as possible and ensuring the basic aesthetic requirements. Oral rehabilitation of an individual can be achieved through simple and inexpensive techniques, even if this increases the time and number of procedures. This has a greater chance of reestablishing itself when there is a collabo-ration between professional and patient, both dedicating themselves towards the same goal.